Analisis Faktor Penentuan Tarif Pelayanan Sambungan Baru Pada Perusahaan Daerah Air Minum (PDAM) Kota Magelang - Shella Bunga Slamet Lantini; Arina Bunganingtyas (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2023)
The PDAM service tariff covers the cost of water treatment, infrastructure management, and services to customers. In PDAM Magelang City, there are several public service tariffs, namely the service of drinking water needs to customers, new connection services, payment of drinking water accounts, water quality inspection services, and water tank services. In this case the author will discuss the public service tariff in the new connection service of PDAM Magelang City.For the research method in this case, the author analyzes the data from the research conducted using descriptive analysis method in which data from interviews and document studies are processed and analyzed to provide an overview of the factors that determine the new connection service tariff at PDAM Magelang City.The new connection service tariff of each PDAM is different, the PDAM Magelang City tariff is based on the customer class which has IV customer groups with different tariffs. The tariff for class I is lower and the tariff will be higher for each class II and so on. Classes are adjusted to the type of house, land area, building area, type of building, type of floor, and type of roof used. The factors for determining the tariff for new connection services at PDAM Magelang City are seen in terms of financial and non-financial factors. In terms of financial factors, it consists of registration fees, drawing planning fees, connection permit fees, transportation costs and construction costs of service and persil pipes. While in terms of non-financial factors in the form of inclusion of new prospective customers on the criteria of the group that has been determined.